1993
DOI: 10.1073/pnas.90.5.2055
|View full text |Cite
|
Sign up to set email alerts
|

Genomic position affects the expression of tobacco mosaic virus movement and coat protein genes.

Abstract: Alterations in the genomic position of the tobacco mosaic virus (TMV) genes encoding the 30-kDa cellto-cell movement protein or the coat protein greatly affected their expression. Higher production of 30-kDa protein was correlated with increased proximity of the gene to the viral 3' terminus. A mutant placing the 30-kDa open reading frame 207 nucleotides nearer the 3' terminus produced at least 4 times the wild-type TMV 30-kDa protein level, while a mutant placing the 30-kDa open reading frame 470 nucleotides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…One possibility was that the deletions caused an increase in expression of other CTV genes, which in turn induced the stem pitting. A common rule of expression of genes of viruses that express multiple genes via subgenomic RNAs is that genes positioned nearer the 3= terminus tend to be produced in larger amounts, and movement of the genes closer to the 3= terminus by deletion of intervening genes increases levels of expression (5). CTV follows this pattern.…”
Section: Discussionmentioning
confidence: 86%
“…One possibility was that the deletions caused an increase in expression of other CTV genes, which in turn induced the stem pitting. A common rule of expression of genes of viruses that express multiple genes via subgenomic RNAs is that genes positioned nearer the 3= terminus tend to be produced in larger amounts, and movement of the genes closer to the 3= terminus by deletion of intervening genes increases levels of expression (5). CTV follows this pattern.…”
Section: Discussionmentioning
confidence: 86%
“…Protoplasts infected with TMV-⌬C and treated with MG115 showed a pattern similar to that for cells infected with wild-type TMV, although significantly more MP was observed in cells infected with TMV-⌬C than in cells infected with wild-type TMV. It was previously shown that TMV lacking the CP produces more MP than does wild-type virus (8). When cells infected with a virus lacking a functional MP were treated with MG115, no MP was detected.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, there was little di¡erence in the amounts of subgenomic mRNAs produced with constructs in which promoters were placed at di¡erent positions in the RNA. The high level of coat protein produced appears to be controlled mainly at the translational level (Culver et al 1993). Whether the same polymerase synthesizes genomic-length and subgenomic RNAs is not known.…”
Section: Regulation Of Tmv Rna Synthesismentioning
confidence: 99%